Detailed sizing optimisation of industrial-scale composite aeronautical structures - Ntourmas, Georgios (2023)
Carbon fibre reinforced polymers have been increasingly used in the aerospace industry over the last decades, because they offer reduced weight and enhanced mechanical characteristics compared to classic metallic structures. However, their application is also linked with several challenges concerning their design and optimisation process. One of the most widely studied topics is the detailed sizing optimisation of variable stiffness composite structures. This task involves determining the optimal thickness and stiffness distribution across the structure and translating that into a manufacturable stacking sequence design. In this study, uni-directional carbon fibre laminae are assumed to be used during manufacturing and therefore the stiffness variation across the span of a composite component is a result of multiple interconnected constant stiffness zones called patches. The task of the detailed design of a composite structure involves the computation of discrete stacking sequences satisfying both mechanical constraints, such as stability and strength, but also design and manufacturing guidelines commonly employed in the aerospace industry. When dealing with industrial-scale structures this optimisation is commonly split up in one gradient and one non-gradient based stage, in order to tackle the challenges of the task. These challenges are associated with mixed continuous and discrete design variables and constraints and the high computational cost of the mechanical constraints. A two stage-optimisation process has also been developed in the framework of this thesis.